Modelagem para estimativa de danos causados aos domicílios por rompimento de barragens: uma aplicação do modelo HEC-FIA ao evento de Fundão - Clarissa Malard Sales (2020)
The Fundão dam failure in Mariana, Minas Gerais, exposed to the Brazilian society a until then unknown problem: the risks that storage mining tailings in dams inflict to the environment and especially to the populations that live near these structures. The risk of a tailings dam is related to the possibility of a structure failure and its potential to cause damage to the environment and society. Brazilian dam safety legislation requires mining companies to submit studies to prove the proper functioning of these structures, as well as a report of causes and consequences, describing material damage to life and property in the event of a breach. Many studies about dam break probability have been conducted, with development, refinement and popularization of capable models to predicting flooded areas in case a dam rupture. However, the related damages are less known or discussed in Brazil. There are many methodologies available in the literature for the classification and estimation of flood damage, whether it comes from a natural event or in case of dam disasters. From the hydrodynamic modeling and the impacted area socioeconomic characterization by the Fundão dam rupture, the present work estimated the direct damage caused to the households in this event. For this, the model developed by the US Army Corps of Engineers named HEC-FIA was used. The results suggested that the application of spatially explicit models, combined with geoprocessing techniques, may contribute to the knowledge of the damage, also to the planning of the areas exposed to the risk of dam rupture and to the planning of emergency actions in the region in case a failure happen.